Using radiocarbon to apportion sources of polycyclic aromatic hydrocarbons in household soot - Reddy, C. M.; Xu, L.; O'Connor, R. (Environmental Forensics, 2003)
To determine whether polycyclic aromatic hydrocarbons (FAHs) in household soot were derived from the combustion of scrap wood or creosote that was impregnated in the wood (or some combination of both), the molecular composition and radiocarbon (C-14) content of the total carbon and several PAHs in the soot was investigated. The 5730-year half-life of C-14 makes it an ideal marker for identifying creosote-derived PAHs (C-14-free) versus those derived from the combustion of wood (contemporary C-14). The C-14 abundance of phenanthrene, fluoranthene, pyrene, and retene was determined by accelerator mass spectrometry after solvent extraction and purification by preparative capillary gas chromatography. The molecular analysis (presence of retene and 1,7-dimethylphenanthrene) and bulk C-14 content (contemporary) of the soot indicated that wood combustion was a strong source of carbon to the soot. The C-14 of retene in two soot samples was also contemporary, indicating that it was derived from the combustion of the scrap wood. These results are consistent with previous work that has suggested that retene is an excellent marker of wood combustion. However, the C-14 content of phenanthrene, fluoranthene, and pyrene in one soot sample was much lower and revealed that these compounds had a mixed creosote and wood source. Using an isotopic mass balance approach, we estimate that 40 to 70% of phenanthrene, fluoranthene, and pyrene were derived from the combustion of the scrap wood. The results of this study show that molecular marker and bulk C-14 analysis can be potentially misleading in apportioning sources of every PAH, and that molecular-level C-14 analysis of PAHs can be a powerful tool for environmental forensics.
731ytTimes Cited:16Cited References Count:42